Ultra-low-dose thoracic CT with model-based iterative reconstruction (MBIR) in cystic fibrosis patients undergoing treatment with cystic fibrosis transmembrane conductance regulators (CFTR). Issue 5 (May 2021) - Moloney, F.; Kavanagh, R.G.; Ronan, N.J.; Grey, T.M.; Joyce, S.; Ryan, D.J.; Moore, N.; O'Connor, O.J.; Plant, B.J.; Maher, M.M.
Abstract : AIM: To assess the utility of a volumetric low-dose computed tomography (CT) thorax (LDCTT) protocol at a dose equivalent to a posteroanterior (PA) and lateral chest radiograph for surveillance of cystic fibrosis (CF) patients. MATERIALS AND METHODS: A prospective study was undertaken of 19 adult patients with CF that proceeded to LDCTT at 12 and 24 months following initiation of ivacaftor. A previously validated seven-section, low-dose axial CT protocol was used for the 12-month study. A volumetric LDCTT protocol was developed for the 24-month study and reconstructed with hybrid iterative reconstruction (LD-ASIR) and pure iterative reconstruction (model-based IR [LD-MBIR]). Radiation dose was recorded for each scan. Image quality was assessed quantitatively and qualitatively, and disease severity was assessed using a modified Bhalla score. Statistical analysis was performed and p -values of <0.05 were considered statistically significant. RESULTS: Volumetric LD-MBIR studies were acquired at a lower radiation dose than the seven-section studies (0.08 ± 0.01 versus 0.10 ± 0.02 mSv; p= 0.02). LD-MBIR and seven-section ASIR images had significantly lower levels of image noise compared with LD-ASIR images ( p< 0.0001). Diagnostic acceptability scores and depiction of bronchovascular structures were found to be acceptable for axial and coronal LD-MBIR images. LD-MBIR images were superior to LD-ASIR images for all qualitative parameters assessed ( p< 0.0001). No significant change was observed in mean Bhalla score between 1-year and 2-year studies ( p= 0.84). CONCLUSIONS: The use of a volumetric LDCTT protocol (reconstructed with pure IR) enabled acquisition of diagnostic quality CT images, which were considered extremely useful for surveillance of CF patients, at a dose equivalent to a PA and lateral chest radiograph. Highlights: CF may be evaluated with CT at a radiation dose equivalent to a chest radiograph. Low dose thoracic CT may be acquired with a mean ED of 0.08 ± 0.01mSv. Compared with ASIR, MBIR images demonstrate superior objective image parameters.